SCHOOL STRATEGIES IN EFFECTIVE ONLINE LEARNING - Ira Guswira; Yantoro Yantoro; Syahrial Syahrial (Institute of Computer Science (IOCS), 2022)
This study aims to determine the readiness of schools to implement effective online learning so that learning materials can be conveyed properly to students. This is because the success of learning effectiveness depends on the strategy carried out by the school in order to achieve a goal to be achieved. The results of this study indicate that the research conducted at SDN 200/IV Jambi City uses the synchronous online method, which means that learning is carried out in real time, namely where the learning carried out between teachers and students is both online at a predetermined time. Which online learning is inseparable from learning media, the media used is adjusted to the current state of learning, currently the media used are laptops, mobile phones, wifi and internet quota as well as applications that can accommodate online learning. Like youtube and whatsapp groups. From the results of the study it can be concluded that the school's strategy in online learning is effective. Based on the conditions of online learning at SDN 200/IV Jambi City has implemented learning well using synchronous online in accordance with the capabilities possessed in operating technology and financial capabilities. Even with a little use of the application and there are obstacles, online learning can still be carried out according to government policy standards.